Growth Stunting Implication in Children: A Review on Primary Tooth Eruption - Setiawan, Arlette S.; Abhista, Nidia; Andisetyanto, Prima; Indriyanti, Ratna; Suryanti, Netty (European Journal of General Dentistry, 2022)
Growth stunting is a form of malnutrition that causes children to have a shorter height for their age. Growth stunting can affect tooth eruption, including delayed deciduous teeth eruption. An electronic search was performed in PubMed and Google Scholar up to December 2020 including the terms related to eruption time of deciduous teeth in stunted children, articles in English and Indonesian, research on humans, research articles, and articles that can be accessed in full text. Articles that were not related to eruption time of deciduous teeth in stunted children, articles published over the last 10 years, articles that only used weight for age indicator as an indicator of malnutrition, and articles with incomplete pages were excluded from the study. Seven cross-sectional articles were included in this study. Three studies assessed the age of deciduous teeth eruption, two studies assessed the number of erupted deciduous teeth in malnourished children, three studies assessed the sequence of deciduous teeth eruption, and six studies assessed the association of nutritional status with deciduous teeth eruption.
Keywords: growth stunting; tooth eruption; deciduous teeth